Outcomes of Endoscopic Therapy for Luminal Strictures in Crohn's Disease. Issue 7 (26th April 2018) - Shivashankar, Raina; Edakkanambeth Varayil, Jithinraj; Scott Harmsen, W; Faubion, William A; Wong Kee Song, Louis M; Bruining, David H; Schroeder, Kenneth W; Kisiel, John; Loftus, Edward V; Coelho Prabhu, Nayantara
Abstract: Backgrounds: We sought to describe the outcomes of endoscopic therapy of luminal strictures in patients with Crohn's disease (CD) at a large tertiary referral center. Methods: All patients who had undergone endoscopic dilation of CD strictures between January 1, 1990 and November 30, 2013 were identified. Demographics, disease characteristics including medication use and history of surgeries, details of endoscopic procedures, and long-term outcomes were analyzed. A successful procedure was defined as ability of the endoscope to pass through the stricture after dilation or effacement of the dilating balloon under fluoroscopy. Kaplan-Meier and Cox proportional hazards analysis were used. Results: For this study 286 index procedures for CD-related stricture dilation were performed in 273 patients (53.8% women) with median age of 45.9 years (range, 14.9–92.2). The most common stricture locations were ileocolonic anastomosis (36.4%) and colon (13.9%). One hundred fourteen (41.8%) patients had a second dilation. The cumulative probability of need for a second dilation following the index procedure was 33.6% at 1 year (95% CI, 25.9%-38.7%), 53.9% at 3 years (45.9%-61.2%), and 60.2% at 5 years (51.4%-67.5%). Six adverse events occurred after the first procedure: 4 perforations, 1 patient with bleeding, and 1 patient with abdominal pain requiring hospitalization. A total of 82 (30%) patients required surgery for their stricture. Conclusions: In a large cohort, endoscopic stricture dilation in CD was safe and effective. About 33% of patients required a second dilation at 1 year after the initial dilation; younger age and smaller inner diameter of the index stricture predicted need for a second dilation.